PERSEPSI MAHASISWA TERHADAP PENGGUNAAN YOUTUBE DALAM PENINGKATAN KOSAKATA - Theresia Katiandagho; Golda J. Tulung; Garryn Ch. Ranuntu (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2022)
Â Â Â Â Â Â PERSEPSI MAHASISWA TERHADAP PENGGUNAAN YOUTUBE DALAMÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â PENINGKATAN KOSAKATAÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Theresia KatiandaghoÂ¹Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Golda J. TulungÂ²Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Garryn C. Ranuntu Â³Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â ABSTRACTÂ Â Â This research is entitled â€œStudentsâ€™ Perception On the Use of YouTube to Develop Their Vocabularyâ€. The objective of the research is to identify, classify and describe the ways English Students use YouTube to develop their Vocabulary. It is also to analyze and describe studentsâ€™ perception on using YouTube to develop their vocabulary. This research used descriptive quantitative method. The research collected the data using questionnaire and interview. The sample was 30 studentsâ€™ from batch 2017 of English Department Faculty of Humanities. Thirty studentsâ€™ responses were collected by online questionnaire with google-form and answer collected by online interview with Whatsapp. The collected data were quantitatively analyzed by presentage formula. Using theory Freeman and Anderson (2011: 250) and to analyze the university studentsâ€™ perception about the use of YouTube to develop their vocabulary base on the theory of Nelson-Smith (2008: 32). The result showed that most of the respondents had positive responses about the use of YouTube to develop their vocabulary. Since YouTube can be used both as providing teaching resource and enhanced learning experience. Based on the findings, it can be concluded that University students have positive perceptions on the use of YouTube in the use of media YouTube is considered useful to the students at Faculty of Humanities, English Department, Sam Ratulangi University_________________________Keywords: University studentsâ€™ perception, Learning Media, YouTube, VocabularyÂ Â¹ Mahasiswa yang bersangkutanÂ² Dosen Pembimbing MateriÂ³ Dosen Pembimbing Teknis